Neurological update: gliomas and other primary brain tumours in adults - Brandner, Sebastian (J Neurol, 2017)
The emerging understanding of molecular changes in a wide range of brain tumours has led to a significant shift in how these tumours are diagnosed, managed and treated. This article will provide a hands-on overview of the relevant biomarkers and their association with newly defined biological tumour entities.